PLANTING THE MORAL VALUES IN INTEGRATED ISLAMIC MIDDLE SCHOOL FITHRAH INSANI - Muhamad Imam Pamungkas; Tiara Lidia Kani (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
Moral is the most important part of the pillars of Islam besides monotheism (tawhid) and the Shari'a. These three aspects are used as the basis of implementation for adherents, both in the application in the family environment, work environment, community environment, even wider environment, namely nation and state. For that reason, of course it is very important for us to know the details related to this character. The focus of this research is on the application and inculcation of moral values in Integrated Islamic Middle School Fithrah Insani, which until now has two branches of education units. This research uses a descriptive-analytic method with qualitative case study type. This research uses primary and secondary data sources. Data collection techniques carried out by interview , observation, literature, and documentation. As a conclusion, it was found that inculcation of moral values in Integrated Islamic Middle School Fithrah Insani was implemented in the activities of Recitation of the Qur'an (TTQ), Mentoring / Character Building, MABIT / CAMP, Assigning Students to Learn and Look for Teachers to Teach Themselves Outside School, and Public Lecture . Keywords: Moral Value, Akhlak, Integrated Islamic School, Fithrah Insani